2017
DOI: 10.1111/ijfs.13478
|View full text |Cite
|
Sign up to set email alerts
|

Using soy protein SiOx nanocomposite film coating to extend the shelf life of apple fruit

Abstract: Preservation properties of soy protein isolate (SPI)/nano‐SiOx composite coatings to apple fruits were investigated. The sodium dodecyl sulfonate‐modified nano‐SiOx (SNS) particles were prepared by the ultrasonic method and the counter‐ion activation method, which products were designated as USNS and CSNS, respectively. The incorporation of CSNS particles was better than USNS to improve the preservation quality of the SPI film. The best conditions for the synthesis of the composite film were as follows: 10% SP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(13 citation statements)
references
References 43 publications
(61 reference statements)
0
13
0
Order By: Relevance
“…Findings of Vejdan, Ojagh, and Abdallohi () also support the present investigation that the addition of TiO 2 nanoparticles in gelatin/agar bilayer films prevented the transmission of UV light through the film and so reduced the rate of photo oxidation of the fish oil during storage. Yu et al () and Liu et al () also reported that the incorporation of nano‐SiOx improved the mechanical and gas barrier properties of the biodegradable film. In the present investigation, nanoparticles containing bilayer film showed a positive effect on the stability of almond oil during storage at intermediate RH.…”
Section: Resultsmentioning
confidence: 95%
“…Findings of Vejdan, Ojagh, and Abdallohi () also support the present investigation that the addition of TiO 2 nanoparticles in gelatin/agar bilayer films prevented the transmission of UV light through the film and so reduced the rate of photo oxidation of the fish oil during storage. Yu et al () and Liu et al () also reported that the incorporation of nano‐SiOx improved the mechanical and gas barrier properties of the biodegradable film. In the present investigation, nanoparticles containing bilayer film showed a positive effect on the stability of almond oil during storage at intermediate RH.…”
Section: Resultsmentioning
confidence: 95%
“…The thickness of each film was measured at five random positions with four at the edge and one at the center of the film using a Type A 130‐01‐410 micrometer (Qinghai Measuring & Cutting Tools, China) with 4 μm accuracy. The five values were then averaged to determine the thickness of each gluten film (Liu et al., ).…”
Section: Methodsmentioning
confidence: 99%
“…Figure 4 shows the advances in the development of nanosystems incorporated with food-grade ingredients, which makes it feasible to explore functional modifications in food coating materials that include nanoemulsions, polymeric nanoparticles, nanostructured lipid transporters, nanotubes, nanocrystals, nanofibers, and others [52]. Nanosystems, when incorporated into matrices based on hydrocolloids (proteins or carbohydrates), give rise to nanocomposites, which are the combination of two or more materials, one of which is on a nanoscale, in order to improve coating properties [52,53]. The main changes due to use of nanosystems in nanocomposite coatings refer to the water barrier, optical and microstructural mechanical properties, and the antimicrobial and antioxidant effects.…”
Section: Nanomaterials In Edible Coatingsmentioning
confidence: 99%